Effect of thermo-hygro glycol aging on the damage mechanisms of short glass-fiber reinforced polyamide 66. (February 2023) - Chekkour, Rabii; Benaarbia, Adil; Chatzigeorgiou, George; Meraghni, Fodil; Robert, Gilles
Abstract: This paper aims at studying the effect of ethylene glycol aging on the overall behavior and the damage mechanisms of the Polyamide 66 (PA66) and the short glass fiber reinforced polyamide 66 (PA66/GF). To this end, a proper experimental aging setup is designed and presented for conditioning the samples in glycol at different aging durations. The glycol absorption effect is analyzed through the swelling and the mass variation (uptake). Moreover, monotonic tensile tests are performed to study the glycol aging effect on the PA66 and PA66/GF. SEM (Scanning Electron Microscopy) investigation is then performed to characterize the damage mechanisms and their evolution with the increase of the aging duration. X-ray micro-computed tomography (µCT) observations are also carried out to quantify the damage depending on the aging duration, the material, and the area of interest (AOI). Experimental findings show that the glycol absorption is more important for the PA66 unreinforced matrix than for the short glass fiber reinforced PA66 composite. In addition, the stiffness, as well as the material deformability, are found to be significantly affected by the glycol aging. In terms of composite degradation, the main damage mechanisms are the damage at fiber's end and the fiber–matrix interface, and for the high aging durations, cavitation in the polymer matrix is observed. The X-ray µCT investigation has indicated pronounced damage mostly located at the core and surface of the samples, which is due to the well-known shell-core microstructure of injected PA66/GF composites. All these conclusions lead to infer the significant and irreversible effect of glycol aging on the bulk mechanical behavior and damage mechanisms of the investigated materials.